2007
DOI: 10.1002/ibd.20285
|View full text |Cite
|
Sign up to set email alerts
|

Guidelines on the diagnosis and management of iron deficiency and anemia in inflammatory bowel diseases#

Abstract: Anemia is a common complication of inflammatory bowel diseases. An international working party has formed and developed guidelines for evaluation and treatment of anemia and iron deficiency that should serve practicing gastroenterologists. Within a total of 16 statements, recommendations are made regarding diagnostic measures to screen for iron- and other anemia-related deficiencies regarding the triggers for medical intervention, treatment goals, and appropriate therapies. Anemia is a common cause of hospital… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
416
1
48

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 400 publications
(473 citation statements)
references
References 54 publications
8
416
1
48
Order By: Relevance
“…We observed that the primary form of iron substitution in our patients was oral substitution (25.9%), followed by intravenous iron (17.9%) and blood transfusions (7.14%); ESA (1.1%) were rarelly used to correct hemoglobin levels and iron deficiency. These results are somewhat inconsistent with the European guidelines recommendations and the data in the medical literature [16]. One of the limitations of this study is the fact that we have not assessed the relationships among disease activity, CRP level and anemia.…”
Section: Discussioncontrasting
confidence: 80%
See 1 more Smart Citation
“…We observed that the primary form of iron substitution in our patients was oral substitution (25.9%), followed by intravenous iron (17.9%) and blood transfusions (7.14%); ESA (1.1%) were rarelly used to correct hemoglobin levels and iron deficiency. These results are somewhat inconsistent with the European guidelines recommendations and the data in the medical literature [16]. One of the limitations of this study is the fact that we have not assessed the relationships among disease activity, CRP level and anemia.…”
Section: Discussioncontrasting
confidence: 80%
“…Anemia therapy should be taken into consideration for every patient with a hemoglobin level below normal [13,14] and iron substitution is recommended for every anemic patient who has iron deficiency [15][16][17]. It is known that treating only the underlying disease is not enough to corect the Hb levels [18].…”
Section: Discussionmentioning
confidence: 99%
“…The anemia common to patients with IBD is mainly due to iron deficiency from blood loss, either alone or in combination, and suppression of erythropoiesis and iron binding (17,18) due to proinflammatory cytokine activity. There has been support for aggressively treating anemia in IBD using iron therapy for those who are iron deficient and using erythropoietin for subjects with impaired red blood cell production (15,(18)(19)(20).…”
Section: Introductionmentioning
confidence: 99%
“…Expert reviews have suggested the use primarily of serum ferritin (with or without transferrin saturation) (18)(19)(20), with some indicating that the addition of sTfR could enhance the ascertainment of iron deficiency in IBD, considering that serum ferritin is an acute phase reactant and thus can be difficult to interpret in the presence of inflammation (19,20). Soluble transferrin receptor (sTfR) is thought to be more sensitive than ferritin at detecting iron deficiency, although the incremental utility of this index continues to be debated (24,25).…”
Section: Introductionmentioning
confidence: 99%
“…ID has an adverse impact on quality of life [6,9,11,12]. Therefore, it is important to carefully evaluate iron status of all patients so that ID and IDA can be diagnosed and treated timely [7,8].…”
Section: Introductionmentioning
confidence: 99%